2020
DOI: 10.1111/dth.13573
|View full text |Cite
|
Sign up to set email alerts
|

Could patients taking isotretinoin therapy be immune against SARS‐CoV ‐2?

Abstract: The coronavirus disease (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is still expanding. Angiotensin-converting enzyme 2 (ACE2) is the key host cellular protein required for SARS-CoV-2 entry. Its expression has been demonstrated in many tissues including alveolar epithelial type II cells in lungs, oral mucosa and intestine, heart, kidney, and endothelium. 1 In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…It has been documented that isotretinoin is a protease inhibitors and can be a taken as a target therapy in COVID-19 (42). After our clinical trial many studies con rmed our suggestion and found that isotretinoin and all trans retinoic acid could protect individuals against COVID-19 complication (43,44,45,46,47,48).…”
Section: I) Part Of Covid-19supporting
confidence: 58%
“…It has been documented that isotretinoin is a protease inhibitors and can be a taken as a target therapy in COVID-19 (42). After our clinical trial many studies con rmed our suggestion and found that isotretinoin and all trans retinoic acid could protect individuals against COVID-19 complication (43,44,45,46,47,48).…”
Section: I) Part Of Covid-19supporting
confidence: 58%
“… 16 On the other hand, it has been claimed that the use of isotretinoin might prevent the cellular entry of SARS‐CoV‐2, since isotretinoin is one of the strongest down‐regulator of ACE‐2 receptors. Moreover, immunomodulatory effects of isotretinoin through inhibition of papain‐like protease, encoded by SARS‐CoV‐2 and a potential target protein in the treatment of COVID‐19, 17 might lower risk of getting COVID‐19 in patients with acne vulgaris 18 . These reports were only comments on the possible effect of isotretinoin on COVID‐19 mostly based on in vitro studies, 17,19 and not supported by real‐world experiences with clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…16 On the other hand, it has been claimed that the use of isotretinoin might prevent the cellular entry of SARS- COVID-19, 17 might lower risk of getting COVID-19 in patients with acne vulgaris. 18 These reports were only comments on the possible effect of isotretinoin on COVID-19 mostly based on in vitro studies, 17,19 and not supported by real-world experiences with clinical studies.…”
Section: Ta B L E 1 Demographics and Clinical Characteristics Of The ...mentioning
confidence: 99%
“…The rationale behind investigating isotretinoin as a candidate for drug repurposing against COVID-19 resides in the following four properties of the drug: (1) modulation of IL-2, interferon γ (IFN-γ) and T and B lymphocyte function, 149 (2) down regulation of ACE2 receptors, 157 which are essential for the viral entry into the host cell, 158 (3) potential inhibition of papain-like protease (PLpro)-protein encoded by SARS-CoV-2 genes, 159 and (4) increase of CD4 counts and marked decrease of viremia in HIV-positive patients. 160 …”
Section: Repurposing Of Dermatologic Medications To Treat Covid-19mentioning
confidence: 99%